Female Circumcision in Malaysia: Challenges and Lessons Learned in Using Focus Groups through an NGO-Academia Collaboration - Nik Mat, Nik Nur Ainin Soffiya; Pillai, Stefanie; Kaur, Surinderpal (Journal of Modern Languages, 2023)
Female circumcision is a relatively understudied topic in the Malaysian context. It is also a topic that is considered sensitive due to its strong association with culture and religion. This paper explores the challenges and lessons learned from a larger project that focuses on the discourse analysis of female circumcision in Malaysia. The project involves collaborative work with a local NGO that works on the advancement of Muslim women’s rights in Malaysia. This paper outlines the processes involved in data collection via focus group discussions and is written as a reflexive exercise based on the recommendations proposed by Olmos-Vega et al. (2023). This reflexive paper on the methodological challenges and lessons learned from the collaboration offers insights that can help other researchers make a more informed research choices on working on collaborative research and on the use of focus groups as a method of data collection.